Use of herbal products for gas pain in children: a questionnaire-based study and alkaloid content analysis - Semih Bulut; Nazmi Mutlu Karakaş; Ayhan İbrahim Aysal; Didem Deliorman Orhan (BMC Complementary Medicine and Therapies)
Abstract Background Herbal products have been used for gas pains in children for many years. However, the quality of herbal products used in children and the presence of contamination in the products are controversial. This study was conducted to evaluate the frequency of use of herbal products for gas pain in pediatric patients, the attitudes of parents towards the use of herbal products, and the pyrrolizidine alkaloid content of herbal products used for gas pain. Methods The survey part of the study was conducted between 15.06.2020–15.09.2020 at Gazi University Hospital Pediatrics Clinics. The surveys were conducted face to face with the parents. The Statistical Package for Social Sciences (SPSS) 23 program was used in the analysis of the data. In the other part of the study, 28 herbal products frequently used in gas pain were purchased from spice shops, markets and internet sites and their pyrrolizidine alkaloid content was evaluated by LC-QTOF-MS analysis. Results 31.5% of the participants had their children use herbal products for gas pains. When the plants used for gas pains in children were examined, fennel came first with a usage rate of 51.3%. The plants used in gas pains were purchased from spice shops by most of the participants (59%). The presence of pyrrolizidine alkaloids above 10 µg/kg concentration was detected in 75% of herbal products used in gas pains. Conclusion In all segments of society, children are given herbal products for gas pains. Parents mostly buy herbal products from spice shops. Products sold for gas pains may cause hepatotoxic effects in children when consumed for a long time and in high doses due to the pyrrolizidine alkaloids they contain. Herbal products to be used in gas pain should be used under the consultancy of a physician/pharmacist and should be obtained from pharmacies.